Implementation of Guided Inquiry Learning to Improve Hydrocarbon Learning Outcomes for Tenth Grade Students in SMKN 2 Palembang - Harlely Rianavita; Muhammad Hadeli L; Meidia Farlina (Pedagogy Review, 2023)
Abstract: Application of Guided Inquiry Learning Model To Improve The Chemical Learning Outcomes of Students in Class X TBSM II SMK N 2 Palembang. This study aimed to improve students’ chemistry learning outcomes through Guided Inquiry learning model in class X TBSM II SMK Negeri 2 Palembang. This study was conducted in two cycles, each cycle consists of two meetings. Data were obtained by using an instrument of observation and test. The finding showed that guided inquiry model was effective to improve student learning outcomes proven by the average student learning outcomes before the action (To) 71,87 with 63.33% learning completeness has increased in cycle I (T1)  become 76.38 with 73.33% learning completeness then more in cycle II (T2) increased become 84.80 with 86.67% learning completeness. Keywords: classroom action research, inquiry learning, student learning outcomes.